Development and Prospect of Edge Intelligence for Industrial Internet - Ren Yaodanjun (《中国工程科学》杂志社, 2021)
As the industrial Internet deeply integrated with manufacturing, the drive capability of industrial intelligence becomes prominent regarding the digitization and informatization of the manufacturing industry. Meanwhile, new applications propose higher requirements for service quality. Edge intelligence, a product of edge computing and artificial intelligence, completes intelligent tasks using computing resources near the data origin. It can alleviate bandwidth transmission pressure, shorten service response delay, and protect the security of private data. Hence, edge intelligence provides a possible approach to satisfy the performance requirements in industrial intelligence applications. This study reviews the research status of cooperative computing, resource isolation, privacy protection, and other key technologies in edge intelligence. Then the typical applications of edge intelligence in equipment management services, production process automation, and manufacturing assistance in the industrial Internet are analyzed in detail. Moreover, the development trend of edge intelligence for the industrial Internet is analyzed in terms of business driving mode, industrial ecology composition, alliance role, and business model. Furthermore, relevant policy suggestions are proposed. We suggest that superior resources should be integrated to establish industry standards; investment increased in basic common resources to deepen the application of the industrial Internet; a good industrial ecology created in the subdivided fields; and university–enterprise cooperation promoted to cultivate interdisciplinary personnel.